Disability support associations in the educational field - Rodríguez Torres, Javier (2022)
In Spain, disability support organizations emerged in the 1950s as a result of the associative movement. Their growth and significance in subsequent decades have turned them into key players in addressing special educational needs and ensuring the principle of equality and non-discrimination in the educational sphere. This study aims to examine, through a bibliographic review, the social role that these entities play in empowerment and dialogue. The findings lead us to the necessity of actively incorporating their functionality into the national educational system, serving as an agent that facilitates the proper distribution of welfare state resources and ensures non-discrimination.